Pengaruh Pengawasan, Beban Kerja, Dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan - Tika Andri Yaningsih; Endang Triwahyuni (Akmenika: Jurnal Akuntansi dan Manajemen, 2022)
This study aims to determine the effect of supervision, workload, and career development on job satisfaction of employees of PT Guna Teguh Abadi (GTA) at JTB-Project Bojonegoero, East Java. The research sample was taken using the Propionate stratified random sampling technique with a total of 73 employees. Data collection techniques were carried out by means of interviews and questionnaires. The analysis technique used in this study uses multiple linear regression analysis with the help of SPSS 21.0 for windows. The results showed that the variables, namely supervision (X1), workload (X2), and career development (X3) were partially and simultaneously affected by job satisfaction (Y), thus all of them supported the four hypotheses. the most dominant influence on job satisfaction.Keywords: Supervision, Workload, Career Development, Job Satisfaction.